1961
DOI: 10.1037/h0047436
|View full text |Cite
|
Sign up to set email alerts
|

The effects of drives conflicting with exploration on the problem-solving behavior of rats reared in free and restricted environments.

Abstract: and Bowling (1960) concluded that the characteristic mazesolving superiority of rats reared in a free environment was due, not to differences in intelligence or in maze-solving ability, but to differences in exploratory behavior. Using males and females reared in both free and restricted environments, they found, first of all, significant correlations between Hebb-Williams error-scores (Rabinovitch & Rosvold, 1951) and exploration measures even when several months intervened between these testings. Secondly, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1976
1976
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(13 citation statements)
references
References 7 publications
1
11
1
Order By: Relevance
“…Early studies in animal models have shown that isolation modulates the behavioral response towards novel stimuli and induces locomotor hyperactivity 44 and leads depletions of NA in diverse brain regions including the hippocampus 45 . Furthermore, sensory deprivation as induced through isolation adversely affects cognition in animals 46 . Although the direct mechanisms underlying deterioration in cognitive performance has not been fully elucidated, it is tempting to speculate that NA might be a driving mechanism due to its important role in the induction of long-term potentiation (LTP) to facilitate memory consolidation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…Early studies in animal models have shown that isolation modulates the behavioral response towards novel stimuli and induces locomotor hyperactivity 44 and leads depletions of NA in diverse brain regions including the hippocampus 45 . Furthermore, sensory deprivation as induced through isolation adversely affects cognition in animals 46 . Although the direct mechanisms underlying deterioration in cognitive performance has not been fully elucidated, it is tempting to speculate that NA might be a driving mechanism due to its important role in the induction of long-term potentiation (LTP) to facilitate memory consolidation 47 .…”
Section: Discussionmentioning
confidence: 99%
“…This learning deficit in isolates was likely due to poorer between-session learning (Amitai et al, 2014; Zeeb, Wong, & Winstanley, 2013). Learning and other cognitive deficits have been observed in isolates in a variety of other tasks, including tests of spatial and working memory (Einon, 1980; Woods, Fiske, & Ruckelshaus, 1961), reversal learning (Jones, Marsden, & Robbins, 1991; Krech, Rosenzweig, & Bennett, 1962; Li, Wu, & Li, 2007; Powell, et al, 2015; Schrijver, Pallier, Brown, & Wurbel, 2004), passive avoidance (Valzelli, 1973), recognition memory (Bianchi et al, 2006), and attentional set-shifting (Schrijver & Wurbel, 2001). …”
Section: Discussionmentioning
confidence: 99%
“…The effects of environmental enrichment on the rats' learning are complicated by their different responses to novelty and their sensitivity to reinforcement and punishment. For example, the effects of enrichment on spatial learning are greater under conditions of high drive (24-36 h food deprivation) than low drive (12-14 h food deprivation) [46]. Under low drive, the isolated rats appear to show greater exploratory behavior than the enriched rats, whereas under high drive both groups show reduced exploratory behavior.…”
Section: Enrichment and Learningmentioning
confidence: 96%